Reflection of inclusive leadership Behaviors in Psychological flourishing within the organization : An exploratory study of the opinions of a sample of employees of the General Directorate of Education in Babylon Governorate - Aliwi Al-Obeidi, Essam; Abbas Hussein, Sahar; hatef Abed Al- Sada, Meethaq (Iraqi Journal for Administrative Sciences, 2024)
The current research aims to identify the nature of the relationship between inclusive leadership Behaviors and Psychological flourishing by surveying the opinions of a sample of employees of in the General Directorate of Education in Babylon Governorate , and in order to achieve this aims , the researchers distributed 415 questionnaires to the research sample, 364 of which were retrieved, which were valid for statistical analysis. 304 questionnaires, with a response rate of 83%. After analyzing them statistically, the results concluded that there is a positive and significant correlation between inclusive leadership Behaviors and Psychological flourishing. As well as having a positive and significant effect of inclusive leadership Behaviors on Psychological flourishing. On this basis, a number of recommendations were made, the most important of which is the necessity to motivate individuals working in the organization under study to possess the skills, capabilities and behavioral capabilities to achieve the goals. With the need to encourage them to adopt inclusive leadership Behaviors approach that leads to laying the foundations that enable them to do the right things at the right times.